Break in the mean and persistence of inflation: a sectoral analysis of French CPI - Laurent Bilke (European Central Bank (ECB), 2005)
This paper uses disaggregated CPI time series to show that a break in the mean of French inflation occurred in the mid-eighties and that the 1983 monetary policy shift mostly accounted for it. CPI average yearly growth declined from nearly 11% before the break date (May 1985) to 2.1% after. No other break in the 1973-2004 sample period can be found. Controlling for this mean break, both aggregate and sectoral inflation persistence are stable and low, with the unit root lying far in the tail of the persistence estimates. However, persistence differs dramatically across sectors. Finally, the duration between two price changes (at the firm level) appears positively related with inflation persistence (at the aggregate level).
Keywords: E31; C12; C22; 330; Inflation persistence; monetary policy; multiple breaks test; sectoral prices; Inflation; Verbraucherpreisindex; Strukturbruch; Schätzung; Frankreich